2014
DOI: 10.1016/j.jalz.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate effects of vascular risk factors on cerebrovascular changes in autopsy‐confirmed Alzheimer's disease

Abstract: We examined the relationships of ante-mortem vascular risk factors to post-mortem cerebrovascular and AD pathologies. Eighty-four AD patients underwent assessment of vascular risk (blood pressure, cholesterol, smoking, cardiovascular disease, diabetes, atrial fibrillation, transient ischemic attack [TIA] or stroke) and later underwent brain autopsy. Given our aim to examine mild cerebrovascular changes (CVC), individuals were excluded if autopsy revealed large stroke. The most common forms of CVC were circle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 50 publications
4
80
1
Order By: Relevance
“…Our findings that multimorbidity is not associated with biomarkers of amyloid deposition are in agreement with previous studies suggesting that Table 3 Association between multimorbidity and abnormal imaging biomarkers in cognitively normal individuals: Mayo Clinic 32 In a clinicopathologic imaging study, 37 subcortical vascular pathology and atherosclerosis contributed to lower cortical GM volume after AD pathology was considered, further suggesting the importance of vascular pathology to neurodegenerative processes. Diabetes mellitus and hypertension have also been associated with brain pathology such as ischemic lesions or atrophy in imaging studies.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Our findings that multimorbidity is not associated with biomarkers of amyloid deposition are in agreement with previous studies suggesting that Table 3 Association between multimorbidity and abnormal imaging biomarkers in cognitively normal individuals: Mayo Clinic 32 In a clinicopathologic imaging study, 37 subcortical vascular pathology and atherosclerosis contributed to lower cortical GM volume after AD pathology was considered, further suggesting the importance of vascular pathology to neurodegenerative processes. Diabetes mellitus and hypertension have also been associated with brain pathology such as ischemic lesions or atrophy in imaging studies.…”
supporting
confidence: 90%
“…Although the exact mechanism for the association of multimorbidity with neuroimaging measures of neurodegeneration cannot be delineated in the current study, we hypothesize that known mechanisms governing the association of chronic diseases, specifically, vascular conditions such as diabetes 30 postmortem 32 biomarkers could be involved in these pathologic processes. In the present study, the most common dyads (i.e., hypertension and hyperlipidemia, hypertension and arthritis, hyperlipidemia and arthritis, hypertension and diabetes mellitus, cancer and hypertension, hyperlipidemia and diabetes mellitus) that were associated with hypometabolism and decreased cortical thickness in AD signature regions all included vascular conditions.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Subsequently, Hughes et al [46] showed that elevated arterial stiffness was related to progressive β-amyloid deposition in the brain of nondemented elderly adults over 2 years. In addition, Bangen et al [47] revealed that the most common forms of cerebrovascular remodeling among patients with AD were atherosclerosis at the circle of Willis and arteriosclerosis. These data emphasize that remodeling of the aorta, elevated central hemodynamic load, and the subsequent damage and dysfunction of intracranial vessels convey a cumulative effect on brain structure and function that contribute to dementias, including AD, with advancing age.…”
Section: Perspectivesmentioning
confidence: 99%
“…Besides that, by using a linear regression statistical approach, we could establish associations without determining normal/abnormal cutoff values in neuroimaging variables, showing that the association of comorbidities with neurodegeneration may be part of a continuum [20,21]. Interactions among vascular risk factors, frequently observed as comorbidities in older adults, are probably implicated in this pathophysiology [22,23]. Multimorbidity has been recognized as an entity by itself, exceeding the simple coexistence of multiple chronic conditions [24].…”
Section: Discussionmentioning
confidence: 97%